Hospital-based surveillance of invasive pneumococcal disease among young children in urban Nepal - Williams, E; Thorson, S; Maskey, M; Mahat, S; Hamaluba, M; Dongol, S; Werno, A; Yadav, B; Shah, A; Kelly, D; Adhikari, N; Pollard, A; et al. (University of Chicago Press, 2009)
Background. Streptococcus pneumoniae is a leading cause of pneumonia and meningitis in young children. Before implementation of the pneumococcal conjugate vaccine in developing countries, there is an urgent need to provide regional epidemiological data on pneumococcal disease among young children hospitalized in urban Nepal. Methods. Children aged 2 months to 5 years who were admitted to Patan Hospital, Kathmandu, with fever and/or suspected pneumonia, meningitis, or bacteremia were recruited. Blood culture specimens were collected from all participants. In cases of suspected meningitis, cerebrospinal fluid specimens were cultured and were tested for S. pneumoniae antigen. Results. A total of 885 children were recruited during the 21-month study period. Of these, 76 (9%) had meningitis and 498 (56%) had pneumonia, on the basis of clinical criteria. Radiographically confirmed pneumonia occurred in 354 (40%), and probable or definite meningitis occurred in 47 (5%). S. pneumoniae was isolated in specimens from 17 (2%) of the children. Serotypes 1 and 12A were isolated most frequently, and only 1 of 17 isolates had a serotype contained in the currently available 7-valent pneumococcal conjugate vaccine. Conclusions. More than 60% of children aged <5 years who were admitted with fever and/or suspecte invasive bacterial disease in urban Nepal had the clinical syndromes of meningitis and/or pneumonia. A new generation of pneumococcal vaccines that prevent infection with a broader range of serotypes may be necessary to most effectively control pneuomococcal disease in young children in Kathmandu.